Polypharmacy in older adults after transcatheter or surgical aortic valve replacement. (14th October 2021) - Rodighiero, J; McDonald, E G; Lee, T C; Piazza, N; Martucci, G; Langlois, Y; Morin, J F; Bendayan, M; Piancova, P; Lantagne, S; Ouimet, M C; Mantzanis, H; et al.
Abstract: Background: Polypharmacy is associated with higher rates of adverse drug events and unplanned hospital visits in medical patients. Little is known about polypharmacy in frail older adults undergoing transcatheter (TAVR) or surgical (SAVR) aortic valve replacement. Purpose: To determine the prevalence and prognostic implications of polypharmacy and potentially inappropriate medications (PIM) following TAVR or SAVR. Methods: A post hoc analysis of the McGill Frailty Registry was conducted. Patients 70 years of age or older who were discharged alive after TAVR or SAVR at two university hospitals were included. Discharge prescriptions were codified and analyzed using the MedSafer electronic tool that has been validated to flag drug interactions and PIMs considering patient-specific comorbidities. Associations with the primary outcome of 30-day all-cause readmission were examined by logistic regression after adjusting for age, sex, Charlson Comorbidity Index, and procedure type. Results: The cohort consisted of 495 patients (52% TAVR, 21% isolated SAVR, 27% combined SAVR). The mean age was 80.1±5.5 years with 52% females. The mean number of medications was 10.2±3.7 with 90% having 5 or more medications. A total of 55 patients were readmitted within 30 days. While the total number of medications was not predictive, three specific PIMs were found to be harmful and one PIM was found to be protective for readmission: clopidogrel with warfarin or heparin (OR 3.99; 95% CI 1.47, 10.82), diltiazem with heart failure (OR 3.16; 95% CI 1.04, 36.41), doxazosin or terazosin with hypertension (OR 6.21; 95% CI 0.99, 38.88), and any proton pump inhibitor (OR 0.47; 95% CI 0.26, 0.86). Of note, the combination of clopidogrel with direct oral anticoagulants was not found to be harmful for readmission. Conclusion: The prevalence of polypharmacy is elevated in older patients undergoing TAVR or SAVR. Specific PIMs, but not total number of medications prescribed, were found to be associated with potentially preventable readmissions. FUNDunding Acknowledgement: Type of funding sources: None.